HISTORICAL LITERACY AMONG PRIMARY SCHOOL PUPILS - Baharuddin Jabar, Ramli Saadon, Khairi Ariffin3 Mohamad Kamal Kamaruddin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study was aimed at identifying the level of historical literacy among year six primary school students. This historical literacy was divided into three main domains: knowledge, skills and value. This study employed the quantitative approach to identify the level of historical literacy in the three domains: knowledge (content of subjects), skills (including thinking skills and specific skills in history, such as historical thinking skills) and values (noble values and specific values in the historical subjects of patriotism). The instrument used in data collection was a questionnaire in a form of test. The research samples were 345 Year Six students. The data was analysed descriptively to identify the level of students’ historical literacy. Research findings indicated that the level of historical literacy among the Year Six school students was modest at 63.76% (53.15% knowledge, 51.83% skills and 86.3% values). The findings of this study could be used by several parties such as Ministry of Education Malaysia (KPM), school administrators, teachers and students.